Prevalence of chronic pain after herniorrhaphy, orchiopexy, and bernardi procedure in children. A retrospective-prospective study - Ya. Semkovych; D. Dmytriiev; P. Rusak; S. Zaporozhan (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2022)
Chronic postsurgical pain (CPSP) is defined as pain that develops or increases in intensity after a surgical procedure and persists for at least three months. Its prevalence rate ranges from 5% to 54%. Aim - to assess the prevalence of CPSP among children at the age of 7-18 years residing in the Precarpathian region at three and six months after herniorrhaphy, orchiopexy and Bernardi procedure. Materials and methods. There were observed 92 children at the age of 7-18 years, who underwent treatment for abdominal wall hernia, cryptorchidism, varicocele, and hydrocele at the surgical department. Children were divided into the following groups: Group 1a included children at the age of 7-12 years with acute pain syndrome in the postoperative period; Group 1b comprised children at the age of 13-18 years with acute pain syndrome in the postoperative period; Group 2a included children at the age of 7-12 years with chronic pain syndrome; Group 2b included children at the age of 13-18 years with chronic pain syndrome. Results. The prevalence of CPSP following surgery among children of the Precarpathian region was found to be 33.7%, with a male predominance (р<0.05). There was an increased need for postoperative pain management with paracetamol in children of Group 2a (р<0.05). The mean scores of the Face, Legs, Activity, Cry, Consolability (FLACC) scale were significantly higher in children of Group 2a, 2b as compared to Group 1a, 1b (р<0.05). The Visual Analogue Scale (VAS) confirmed greater pain intensity in children of Group 2a on the second and third days of treatment (р<0.05). Conclusions. The high prevalence of chronic pain in children after herniorrhaphy, orchiopexy by Petrivalsky / Schoemaker technique, Ross and Bernardi procedures is due to ineffective perioperative pain management that requires the use of additional analgesia techniques, including regional ones.The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of the participating institution. The informed consent of the patient was obtained for conducting the studies.No conflict of interests was declared by the authors.